Contributions to the Andean Senecioneae (Compositae)—I. Two new species of Werneria - Calvo, Joel; Beltrán, Hamilton (Phytotaxa, 2019)
Two new species of Werneria are described from the central Andes. Both species are compared with the morphologically closest taxa and useful characters for their proper identification are provided. Detailed pictures of living plants and a distribution map are also presented.